The Role of Steam Education in Improving Student Collaboration and Creativity: A Case Study in Madrasah - Qiqi Yuliati Zaqiah; Aan Hasanah; Yeti Heryati (Jurnal Pendidikan Islam, 2024)
The 21st century is marked by increasing technological progress and productivity. This progress has provided a challenge for the education sector to produce quality young people with adequate skills. This research examines the effectiveness of a learning approach that integrates a multi-subject called STEAM, namely science, technology, engineering, arts and mathematics, to improve 21st-century skills. These skills include collaboration, creativity, critical thinking and communication, known as the 4Cs. As a case study, this STEAM learning was given to students at two State Madrasahs in West Java. To achieve this goal, mixed methods were used. The research combined qualitative and quantitative approaches. A qualitative approach was used to observe phenomena experienced by students, learning design, and implementation. Moreover, a quantitative approach was used to analyze the impact of STEAM learning on student skills. The STEAM learning design was delivered in three learning meetings. Research findings show that the STEAM learning model by using a multi-subject approach could significantly improve students' collaboration skills. However, it did not significantly improve students’ critical thinking, creativity and communication skills. Meanwhile, student responses showed positive results on the implementation of this model. Factors that were considered to influence the implementation of this model are: Duration of learning, literacy skills and student learning experiences, as well as teacher competencies.